PENGARUH SELF ESTEEM DAN SOCIAL SUPPORT TERHADAP RESILIENSI AKADEMIK MAHASISWA DENGAN SELF EFFICACY SEBAGAI VARIABEL MEDIASI - Theresya, Doristin; Setiyani, Rediana (Jurnal Ekonomi dan Pendidikan, 2022)
This study aims to analyze the effect of self-esteem and social support on academic resilience through self-efficacy as a mediating variable. This study uses a quantitative approach. The population of this study were 419 students of Economics Education Faculty of Economics, State University of Semarang. The sample was determined using the Slovin formula and obtained as many as 205 students. The sampling technique used is the proportional random sampling technique. The data collection method used is a survey method with data collection techniques, namely questionnaires using google form tools. The data analysis technique used descriptive statistical analysis, and path analysis. The results showed that social support had no effect on academic resilience, but self-esteem and self-efficacy had a positive effect on academic resilience. There is a positive influence of self-esteem, social support on self-efficacy. There is a positive influence of self-esteem and social support on academic resilience through self-efficacy. Self-efficacy can mediate the effect of self-esteem and social support on academic resilience.